(untitled) (Papeles, 2023)
The local stories of Social Service allow us to get closer to the particularities and riches that the professionalization process included in specific contexts of our country. Particularly in Santa Fe, the School of Social Service opened its doors in 1943. Although this profession has historically been linked to the interventional nature, the investigative dimension has occupied a place of relevance that needs to be known and made visible. From the beginning of the training, its protagonists disputed spaces and meanings regarding the place of knowledge production in the incipient profession. For this, we recover background information that allows us to reflect on how the dimension of research has been incorporated into the professional training of the Santa Fe Social Service, from its beginnings to the institutional management of an important actress: Ángela Teresa Vigetti. Likewise, we recover some contributions and proposals from said protagonist in relation to delimitations of the research field, the place of research in Social Service and the imprint of the practical usefulness of knowledge to improve the conditions of existence.